Productive and Reproductive Performances of Female Etawah Crossbred Goats in Indonesia - Sutama, I Ketut (Indonesian Animal Sciences Society, 2009)
Although Etawah Crossbred (PE) goat is considered to be dual purpose (meat and milk) goat, it is mainly raised for meat production. Since early 1990, there has been a growing interest of the farmer in some places to raise PE goat for milk production without sacrificing its role to produce kids for meat. The average birth weight of PE kids varied widely (2.8 â 5 kg), resulted in a high variation in weaning weight (9 â 14 kg). A high pre-weaning mortality of 10 â 50% was a major source of lost in goat production in Indonesia, partly due to low birth weight and/or miss mothering ability. Young female PE goat reached puberty at 8 â 12 months of age and at body weight of about 18 â 22 kg or about 53 â 60% of mature body weight. Gestation length varied between 142 â 156 days, and first post partum estrous occurred at 3 â 5 months after parturition took place, resulted in 8 â 10 months of kidding intervals. Lactation period lasted for 5 â 8 months with total milk yield of 177 â 203 kg/lactation (average 0.85 kg/day). Although milk yield of PE goat was not as high as milk yield of some other dairy goats, the ability of PE goat to cope with harsh local environment, particularly climate and feed conditions, was an advantage. Therefore, raising PE goat would still be an important part of farmer activities in the rural areas in Indonesia.Â Key words: PE goat, reproduction, milk production